The effect of lockup and persuasion on online investment decisions: An experimental study in ICOs - Moritz T. Bruckner; Dennis M. Steininger; Jason Bennett Thatcher; Daniel J. Veit (Electronic Markets, 2023)
Many firms use social media (SM) to solicit online investments. In this study, we examine the interaction between SM attributes and online-investment attributes to determine how this interaction shapes users' investment decisions. Specifically, we investigate initial coin offerings (ICOs) as an application domain of distributed ledger technology for peer-to-peer investment. We use signaling theory to develop a context-specific explanation for how the interplay of persuasion signals found in SM and technology-enforced lockups shapes individuals' ICO investment decisions. To evaluate this interplay, we conducted a 20.167em0.167em2 factorial experiment with 473 participants. The results show that when an investment does not require a technology-enforced lockup, persuasion signals encourage investments in ICOs; however, when an investment requires a technology-enforced lockup, persuasion signals do not affect investments in ICOs. Furthermore, our analyses suggest that combining a technology-enforced lockup and persuasion signals reduces the ICO's plausibility. This is the first study to investigate how the willingness to invest in ICOs is influenced by the relationship between technology-enforced lockups and persuasion signals. The findings have practical implications for individuals attempting to make sound decisions on ICO investments, policymakers regulating online investments, and firms seeking to attract investors.
Keywords: G23; G28; G41; M13; M37; 620; Fintech; Technology-enforced lockup; Persuasion signals; Intention to invest; Plausibility; Social media; Experiment